1908
DOI: 10.1037/h0075841
|View full text |Cite
|
Sign up to set email alerts
|

Studies from the Bryn Mawr college Laboratory. The effect of the brightness of background on the appearance of color stimuli in peripheral vision.

Abstract: The present investigation is a direct continuation of one carried out in 1903-4 in the Mt. Holyoke laboratory. 1 The results of this earlier paper were based on observations of the appearance of the colors at the red-yellow end of the spectrum when seen in peripheral vision, and were in brief as follows :I. The brightness of a colorless background has a decided effect: (1) On the limits for yellow and orange, the limits for the former color being much wider with the darker grounds, for the latter color wider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1958
1958
1965
1965

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A tone previously reported unheard is shut off; this change is then reported by S in experiments by Dunlap (47), Dunlap and Wells (48), and Jastrow (91). Colored afterimages to color reported unseen were obtained by Fernald (59), challenged by Titchener and Pyle (183), and reaffirmed by Ferree and Rand "under the right conditions" (60, p. 196). These results were again obtained by the same authors (61), and by Newhall and Dodge, who found that "thresholds for after-images were lower than for stimulus color" (128, p. 8).…”
Section: )mentioning
confidence: 85%
“…A tone previously reported unheard is shut off; this change is then reported by S in experiments by Dunlap (47), Dunlap and Wells (48), and Jastrow (91). Colored afterimages to color reported unseen were obtained by Fernald (59), challenged by Titchener and Pyle (183), and reaffirmed by Ferree and Rand "under the right conditions" (60, p. 196). These results were again obtained by the same authors (61), and by Newhall and Dodge, who found that "thresholds for after-images were lower than for stimulus color" (128, p. 8).…”
Section: )mentioning
confidence: 85%